Management v krizah: Izbrana poglavja (University of Maribor Press, 2022)
Crisis Management: Selected Chapters. The involvement of the individual in the organization means one of the paths of socialization, which is a sequence of educational paths and other paths that a person takes. Joining the organization means aligning one’s own needs with the goals of the organization, which are assumed according to the vision and strategy and mission of the organization. Here, too, certain routes are outlined at the entrance. And it is not a problem to move or develop them in a way that follows the development tendencies of the organization. However, as in the life of the individual, in organizations the influence of internal and external factors is an eternal companion and a stimulus to reflection - where else?